Effects of shelf bar assistance on kinetic control during sit-to-stand in healthy young and elderly subjects. (9th June 2020) - Sekiguchi, Yusuke; Honda, Keita; Phakdepiboon, Thitiporn; Jinde, Mao; Kato, Tomohisa; Kanetaka, Hiroyasu; Izumi, Shin-ichi
Abstract: This study aimed to determine the kinetic effects of using unilateral shelf bar, vertical grab bar (GB), and horizontal GB during sit-to-stand (STS) in young and elderly subjects. Twenty young adults aged 20–40 years and eighteen healthy elderly people aged ≥ 65 years old were recruited. The subjects performed STS with and without using the three types of bars. Bar reaction force (BRF) and maximum power (MP) defined as the maximal product calculated by multiplying the GRF and the velocity of the center of mass in each direction were measured using three-dimensional motion analysis, two load sensors of GB, and four force plates. The use of the shelf bar generated a significantly larger BRF in the vertical direction than the other bars (p < 0.05) and lower MP in the vertical direction than the horizontal bar (p < 0.05) and no bar (p < 0.05). In the younger subjects, only the use of the vertical bar generated a significantly larger BRF (p < 0.05) and negative MP (p < 0.05) in the forward direction than those in elderly subjects. The use of the shelf bar may assist the decreased MP in the vertical direction during STS in elderly people, resulting in decrease of failed STS in daily living. In contrast, the use of the vertical bar in the elderly may not generate sufficient BRF in the forward direction because of lack of eccentric control in the whole body in the forward direction during STS.